Pengaruh Profitabilitas, Current Ratio, Total Asset Turnover, dan Debt To Equity Ratio Pada Perusahaan Property dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2017 – 2021 - Kamil, Zaidanil; Pranjoto, Raden Gatot Heru (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This study aims to examine the effect of factors Return On Equity, Current Ratio, Total Assets Turnover, Debt To Equity Ratio.The population in this study are all property dan real estate companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique used purposive sampling and obtained 10 companies that became the research sample. The analytical technique used in this research is multiple linear regression analysis. The results of this study indicate that Return On Equity, Current Ratio, Total Asset Turnover,  Debt To Equity Ratio together have a significant effect on the price book value with an R Square of 62.6%. While individually, Return On Equity has a negative and insignificant effect on price book value, while Debt to Equity Ratio and Current Ratio have a positive and significant effect on price book value.